2000
DOI: 10.1111/j.1553-2712.2000.tb00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intravenous Midazolam with Pentobarbital for Sedation for Head Computed Tomography Imaging

Abstract: Abstract. Objective:To compare the efficacy of intravenous (IV) midazolam with that of IV pentobarbital when used for sedation for head computed tomography (CT) imaging in emergency department (ED) pediatric patients. Methods: Prospective, randomized clinical trial in an urban children's hospital. During a two-and-a-half-year period, 55 patients were enrolled: 34 males and 21 females. Measurements included induction time, recovery time, efficacy, side effects, complications, and failure with each drug. Success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…Further studies of pentobarbital sedation for CT scans in children have shown the mean induction times (time from administration to achievement of sufficient sedation to perform the scan) to range from 6 to 8.1 minutes and the mean sedation time (time from induction to discharge) to range from 56 to 86 minutes. 9,10 The use of a sedative agent with a shorter duration of action should improve efficiency in radiology departments and shorten patient recovery time. Furthermore, with the advent of helical CT scanners, the time required to perform CT scans (table times) has been markedly reduced.…”
mentioning
confidence: 99%
“…Further studies of pentobarbital sedation for CT scans in children have shown the mean induction times (time from administration to achievement of sufficient sedation to perform the scan) to range from 6 to 8.1 minutes and the mean sedation time (time from induction to discharge) to range from 56 to 86 minutes. 9,10 The use of a sedative agent with a shorter duration of action should improve efficiency in radiology departments and shorten patient recovery time. Furthermore, with the advent of helical CT scanners, the time required to perform CT scans (table times) has been markedly reduced.…”
mentioning
confidence: 99%
“…20 Although it has an established record of safety and effectiveness and has been demonstrated to be superior to sedatives such as chloral hydrate and midazolam, [21][22][23] its sedation time is long (80-100 minutes). 22 This length of time might be related to the relatively large dose of the drug needed to induce an immobile state. It is usually longer than the time needed for most radiologic procedures, including MRI.…”
Section: Discussionmentioning
confidence: 99%
“…With a success rate of 96%, our results favorably compare with the results reported with other techniques. Indeed, since the introduction of modern imaging (CT and MRI), radiologists and pediatricians have attempted to determine the most effective and safest sedation strategy [14][15][16][17], barbiturates (pentobarbital [5,11,18], methohexital [19][20][21] or thiopental [22][23][24]) and a number of other compounds like chloral hydrate [6,18,25], etomidate [26] and propofol [4,27,28] have been tested (Table 6). With these protocols, sedation has been reported to be effective in 80-100% of patients.…”
Section: Discussionmentioning
confidence: 99%